Intermittent versus dispatchable power sources: An integrated competitive assessment - Gunther Glenk; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The cost and revenue earnings potential of alternative power generation sources has shifted considerably in recent years. Here we introduce the concept of Levelized Profit Margins (LPM) to capture the changing unit economics of both intermittent and dispatchable generation technologies. We apply this framework in the context of the California and Texas wholesale power markets. Our LPM estimates indicate that solar photovoltaic and wind power have both substantially improved their competitive position over the years 2012-2019, primarily due to falling life-cycle costs of production. In California, these gains far outweigh an emerging 'cannibalization' trend that results from substantial additions of solar power having made energy less valuable in the middle of the day. We also find the competitiveness of natural gas power plants to have either improved or held steady. For this generation technology, declining capacity utilization rates have effectively been counterbalanced by a 'dispatchability price premium' that reflects the growing market share of intermittent renewables.
Keywords: M1; O33; Q41; Q42; Q48; Q54; Q55; 330; Renewable Energy; Intermittency; Dispatchable Power; Levelized Cost; Profit Margins